2021
DOI: 10.3389/fcell.2020.618341
|View full text |Cite
|
Sign up to set email alerts
|

PRSS1 Upregulation Predicts Platinum Resistance in Ovarian Cancer Patients

Abstract: Ovarian cancer is the most frequent cause of death among gynecologic malignancies. A total of 80% of patients who have completed platinum-based chemotherapy suffer from relapse and develop resistance within 2 years. In the present study, we obtained patients' complete platinum (cisplatin and carboplatin) medication information from The Cancer Genome Atlas database and then divided them into two categories: resistance and sensitivity. Difference analysis was performed to screen differentially expressed genes (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…In recent work, using immunostaining and fluorescent imaging, the authors revealed that the gene PRSS1 was overexpressed in the endoplasmic reticulum of a high-grade serous ovarian cancer cell line [ 55 ]. Moreover, overexpression of this gene predicts platinum resistance in OC patients [ 56 ]. Downregulation of HMCN2 was recently associated with the inhibition of cell invasion [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent work, using immunostaining and fluorescent imaging, the authors revealed that the gene PRSS1 was overexpressed in the endoplasmic reticulum of a high-grade serous ovarian cancer cell line [ 55 ]. Moreover, overexpression of this gene predicts platinum resistance in OC patients [ 56 ]. Downregulation of HMCN2 was recently associated with the inhibition of cell invasion [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The topmost ranked genes uncovered for the PD doublets include CDCA3, PLK1, NEK2 and FAM64A (table 1) which are involved in ovarian cancer cell proliferation and drug resistance [30][31][32][33]. Furthermore, the topmost ranked genes in CR doublets included PRSS1, ECE1 and UBE2C, which promote ovarian cancer chemoresistance and progression [34][35][36]. Interestingly, MT1G, a tumour suppressor metalloprotein [37,38] was also upregulated in the CR doublets (table 1).…”
Section: Topic Modelling Of Doublets Depicts Interaction-related Gene...mentioning
confidence: 99%